The quotable guide to punctuation - Spector, Stephen 1946- (Oxford University Press, 2017)
This book makes punctuation more fun and easier to learn than traditional approaches do. It teaches the natural way, by example: each lesson begins with quotes that exemplify good punctuation and sentence structure. Quotations are humorous and informative, drawn from the words of notable figures--Shakespeare, Mark Twain, Jerry Seinfeld, Taylor Swift, Beyoncé, Jennifer Lawrence, and many others. Short essays accompany each lesson, showing how each punctuation mark originated and how its use has altered over time. Correct punctuation is vital for clear, accurate, and natural writing. Anyone preparing a course assignment, applying for a job or for college admission, or doing any other formal writing needs to know the standard conventions of punctuation. Yet many people have never been taught how to punctuate. A necessary addition to any writer's bookshelf, this enjoyable book will teach readers to punctuate effectively and confidently--through over 500 memorable quotes and clear explanations of the rules." -- Provided by publisher.